1997
DOI: 10.1021/je960351m
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivities of Some Organic Solvents and Their Binary Mixtures

Abstract: The thermal conductivity of 12 pure organic solvents, acetone, acetonitrile, acrylonitrile, carbon tetrachloride, chloroform, 1,2-dichloroethane, ethanol, ethyl acetate, heptane, tetrahydrofuran, toluene, and water, and eight binary mixtures, acetone + ethanol, acetone + ethyl acetate, ethanol + heptane, ethanol + carbon tetrachloride, ethyl acetate + ethanol, heptane + acetone, heptane + toluene, and water + ethanol, were measured by an absolute transient hot-wire method at some selected temperatures from 253… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…65 For example, in the normal phase mode ( Figure 5B), the thermal conductivity of the heptane−ethanol mixture is approximately 0.13 W/m°C. 66 At low linear velocities, (1.67 mm/s or 1 mL/min, ΔP = 80 bar), the magnitude of the maximum radial temperature difference is 1°C; however, as the linear velocity is increased to 5 mm/s (3 mL/min), the pressure drop is significant (250 bar), and the calculated maximal radial temperature gradient is 8°C. Note that eq 1 is generally used for first order approximations, it has been shown that the calculated radial temperature gradients can overestimate the observed radial gradients because it ignores the compressibility of the eluent.…”
Section: Analytical Chemistrymentioning
confidence: 93%
“…65 For example, in the normal phase mode ( Figure 5B), the thermal conductivity of the heptane−ethanol mixture is approximately 0.13 W/m°C. 66 At low linear velocities, (1.67 mm/s or 1 mL/min, ΔP = 80 bar), the magnitude of the maximum radial temperature difference is 1°C; however, as the linear velocity is increased to 5 mm/s (3 mL/min), the pressure drop is significant (250 bar), and the calculated maximal radial temperature gradient is 8°C. Note that eq 1 is generally used for first order approximations, it has been shown that the calculated radial temperature gradients can overestimate the observed radial gradients because it ignores the compressibility of the eluent.…”
Section: Analytical Chemistrymentioning
confidence: 93%
“…This greatly exceeds the limits of the EOS (50 MPa), and we recommend the correlation be limited to 50 MPa. We estimate the uncertainty for viscosity in the gas phase to be 5 %, and in the liquid phase also 5 % along the saturation boundary, rising to 10 % at pressures up to 50 MPa for temperatures above 270 K. The thermal conductivity was fit to the data of Vines and Bennett (Vines & Bennett, 1954), Mashirov and Tarzimanov (Mashirov & Tarzimanov, 1974), and Qun-Fang et al (Qun-Fang, Ruisen, Dan-Yan, & Yu-Chun, 1997); the resulting coefficients are reported in Table 3, and the parameters for the critical enhancement are in Table 4. All data are in the gas phase except for the limited data of Qun-Fang et al (Qun-Fang et al, 1997) that are for the saturated liquid.…”
Section: R1243zf (333-trifluoropropene)mentioning
confidence: 99%
“…The estimated uncertainty in the gas phase is also 5 %. For thermal conductivity, the gas-phase data of Medzhidov and Safarov ______________________________________________________________________________________________________ (Medzhidov & Safarov, 1983) and the liquid-phase data of Mallan et al (Mallan, Michaelian, & Lockhart, 1972) and Qun-Fang et al (Qun-Fang et al, 1997) were used to obtain the coefficients in Table 3. Parameters for the critical enhancement are presented in Table 4.…”
Section: Acetonementioning
confidence: 99%
“…4, the results for the ethanol/water mixture are also in good agreement with the previous reports. 16,17 The measured thermal conductivity and heat capacity show maximum deviations of 6.2% and 8.0%, respectively. Considering that the results in Table I and Fig.…”
Section: Resultsmentioning
confidence: 97%
“…These results thus prove that the present technique is effective for nanoliter-scale thermal analysis. It is noted that the conventional transient hot-wire method 16 and the micro-differential-scanning-calorimetry 17 require sample volumes of the order of 100 ml and 10 l, respectively. Experiments to monitor the real-time thermal-property variation were performed by injecting air, water, and ethanol through the microchannel.…”
Section: Resultsmentioning
confidence: 99%